Technology Spillovers and Stability of International Climate Coalitions - Miyuki Nagashima; Rob Dellink (Fondazione Eni Enrico Mattei (FEEM), 2007)
Cooperation in international environmental agreements appears difficult to attain because of strong free-riding incentives. This paper explores how different technology spillover mechanisms among regions can influence the incentive structures to join and stabilise an international agreement. We use an applied modelling framework (STACO) that enables us to investigate stability of partial climate coalitions. Technology spillovers to coalition members increase their incentives to stay in the coalition and reduce abatement costs, which leads to larger global payoffs and a lower global CO2 stock. Several theories on the impact of technology spillovers are evaluated by simulating a range of alternative specifications. We find that while spillovers are a good instrument to improve stability of bilateral agreements, they cannot overcome the strong free rider incentives that are present in larger coalitions. This conclusion is robust against the specification of technology spillovers.
Keywords: C72; O33; Q54; 330; Climate Change Modelling; International Environmental Agreements; Non-cooperative Game Theory; Technology Spillovers; Klimaveränderung; Umweltplanung; Internationale Umweltpolitik; Nichtkooperatives Spiel; Technologie; Spillover-Effekt; Theorie; Welt